Gestión de la comunicación de Barcelona Sporting Club 2020 - Campuzano Suñiga, Yomira Susana (2021)
This case study is framed in making known the communication management of Barcelona Sporting Club 2020, in order to determine the content consumption of the social networks Instagram and Facebook in Barcelona, it is important to mention that through an interview, Observation sheet and comparative sheet evidence of the management of the Ecuadorian club and the management of its content on social networks, which demonstrated the great reception that Barcelona has compared to other institutions in the country. Football not only unites masses, but also leaves great economic income both personally and collectively since when participating in international tournaments the commissions are high which helps to keep a sports club in good condition, for its different economic prices, so much so that it is for this very reason that different famous clubs seek to attract attention by bringing in important figures from abroad for high-level competitions. In itself, this research will allow to expose which are the official contents that the organization and design of the various platforms and web pages manage in the fragment of the formation of the corporate image. In addition, recognize the profiles of the audiences that consume social networks such as Instagram and Facebook. For such, detect the increase and competitiveness of the social networks of Barcelona with that of other groups.